Worker and firm heterogeneity, agglomeration, and wages in Brazil. Issue 1 (15th October 2021) - Silva, Diana; Azzoni, Carlos
Abstract: This paper analyses the influence of agglomeration and spatial sorting on wages in Brazilian cities. The empirical strategy is based on a two‐step estimation. The first step estimates a wage equation with the observed characteristics of workers and firms and location effects. The second step decomposes the location effects into employment density and fixed effects of firm and worker. We estimate an urban wage premium for a developing country with the simultaneous inclusion of worker and firm fixed effects, instrumental variables, and nighttime lights. We find agglomeration effects of 4.3–5.7%, which are larger than those obtained for developed countries. Resumen: Este artículo analiza la influencia de la aglomeración y la distribución espacial en los salarios en las ciudades brasileñas. La estrategia empírica se basa en una estimación en dos etapas La primera etapa estima una ecuación salarial con las características observadas de los trabajadores y las empresas y los efectos de ubicación. La segunda etapa descompone los efectos de ubicación en densidad de empleo y efectos fijos de empresa y trabajador. Se estimó una prima salarial urbana para un país en desarrollo mediante la inclusión simultánea de efectos fijos de empresa y trabajador, variables instrumentales e iluminación nocturna. Se encontraron efectos de aglomeración entre el 4, 3 y el 5, 7%, que son mayores que los obtenidos para países desarrollados. 抄録: 本稿では、集積と空間ソーティングがブラジルの都市部の賃金に及ぼす影響を分析する。2段階推定法に基づいた実証的方法を用いる。第1段階は、労働者と企業の特性と立地効果を用いて賃金方程式を推定する。第2段階では、立地効果を雇用密度と企業と労働者の固定効果に分解する。労働者と企業の固定効果、操作変数、夜間光を同時に包含して発展途上国の都市賃金プレミアムを推算する。集積効果は4.3 5.7%であり、先進国の推定値よりも大きい値であった。